Культура як культуроподібність - Пригода, Т. М.; Prigoda, T. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Стаття присвячена феномену постсучасної культури в контексті сучасного культурологічного дискурсу. Культуру проаналізовано як своєрідну систему культурних кодів, шифрів, знаків. Абсолютизуючись, ці про- цеси в подальшому призводять до деградації безпосереднього «живого» поля культури. Культура стає культу- роподібною реальністю, симулятивним простором, утрачаючи автентичні цінності. Звернуто увагу на постгу- маністичні виміри етичних проблем. Article is devoted to the problems of contemporary (postmodern) cultural space. Emphasizes simulative – semiotic content fundamental cultural and civilizational values. Culture is presented as a similarity of culture in all its key areas. Defining ethical constants modern man undergo deep transformations, depriving them of spiritual and existential proper characteristics, becoming episodic, but recognizable signs post-human habitat. Moral categories, losing historical rationalistic and idealistic content pragmatic ability to demonstrate the transformation in local practices polyvariant existence. Current state of culture implies spiritual and practical efforts of a particular person, focused on universal integrity of the surrounding world.
Culture as a Similarity of Culture
Keywords: культура; culture; постсучасність; modernism; людина; people; знак; постгуманізм; humanizm